4-BIT LOW POWER ALU DESIGN USING VHDL - Mahjabi Begum (International Journal of Research Science and Management, 2018)
In this paper, we will learn how to design a low power ALU using VHDL. Advancement in VLSI technology has allowed following Moore’s law for doubling component density on a silicon chip after every three years. An enhancement in the basic function of a transistor has, thus, allowed for designs to be implemented using fewer transistors and reduced interconnections. In published literature, many integrated circuits have been reported which are using multi-input floating gate MOSFETs in standard CMOS process. Thus using the advanced VLSI technology the proposed ALU design is more efficient.